DNA barcodes and morphology revealed three species masquerading in Xiphydria camelus of authors (Hymenoptera, Xiphydriidae) in Northeast Asia: X. eborata sp. rev. and X. albopicta sp. nov. - Shinohara, Akihiko; Kameda, Yuichi (Zootaxa, 2019)
Taxonomic status of the widely spread xiphydriid woodwasp Xiphydria camelus (Linné, 1758) was revised by examining morphology of 964 specimens and by molecular analysis using COI barcode sequences. Both morphological and molecular approaches indicated existence of three separate species masquerading in X. camelus of authors in East Asia. The three species were finally determined as X. camelus, X. eborata Konow, 1899, and a new species, X. albopicta. Xiphydria eborata is revived from synonymy with X. camelus and X. albopicta is described as a new species from Russia (Primorskij Kraj), China (Heilongjiang) and Japan (Hokkaido). Collection records are given for all the specimens examined.